Jump to content
BrainDen.com - Brain Teasers
  • 0
Sign in to follow this  
Pickett

Question

First off, sorry if this has been posted. I haven't seen it on here, and searching for this one was difficult (since "MI" and "MU" are both under 3 letters, and the search doesn't like that...). So again, I apologize if this is a duplicate.

Can you use only the following 4 rules to convert MI to MU?

1) xI --> xIU

2) Mx --> Mxx

3) xIIIy --> xUy

4) xUUy --> xy

Please note: "x" and "y" are placeholders for any string of characters. For example, MUUI would match rule 1 (x=MUU), rule 2 (x=UUI), or rule 4 (x=M, y=I)

Also note: the unidirectional nature of the rules...meaning you CANNOT go from MUU to MIIIU using rule 3...you can only go from MIIIU to MUU.

Also: Before anyone asks, you can use the rules as many or as few times as you like, but you can ONLY use those 4 rules.

I like to use the convention of XXX --#--> YYY where "XXX" is the start string, "#" is the rule number used, "YYY" is the resulting string. So here's a quick example showing a valid conversion:

Convert MUI to MIU

MUI --1--> MUIU --2--> MUIUUIU --4--> MUIIU --1--> MUIIUUIIU --4--> MUIIIIU --3--> MUUIU --4--> MIU

Anyways, this is a classic puzzle. Hope this makes sense! Good luck!

Share this post


Link to post
Share on other sites

3 answers to this question

Recommended Posts

  • 0
Guest

"MI"

(2) M --> M[iI]

(2) M[iI] --> M[iIII]

(1) [MIII]I --> [MIII]IU

(3) [MI]III --> [MI]U

(2) M[iUU] --> M[iUUIUU]

(4) [MIIUUI]UU[] --> [MIIUUI][]

(4) [MII]UU --> [MII]

(3) [M]III[] --> [M]U[]

"MU"

Share this post


Link to post
Share on other sites
  • 0

"MI"

(2) M --> M[iI]

(2) M[iI] --> M[iIII]

(1) [MIII]I --> [MIII]IU

(3) [MI]III --> [MI]U

(2) M[iUU] --> M[iUUIUU]

(4) [MIIUUI]UU[] --> [MIIUUI][]

(4) [MII]UU --> [MII]

(3) [M]III[] --> [M]U[]

"MU"

This is not a correct answer. Very good try.

"MI"

(2) M --> M[iI]

(2) M[iI] --> M[iIII]

(1) [MIII]I --> [MIII]IU

(3) [MI]III --> [MI]U

(2) M[iUU] --> M[iUUIUU]

(4) [MIIUUI]UU[] --> [MIIUUI][] - You added an extra "I" after the "M" between these two steps.

(4) [MII]UU --> [MII]

(3) [M]III[] --> [M]U[]

"MU"

Share this post


Link to post
Share on other sites
  • 0
Guest

No. It is impossible to transform MI to MU using only the 4 given rules.

Of rules 1 and 3, the number of I's does not change.

Of rule 2, the number of I's is multiplied by 2.

Of rule 3, the number of I's is decreased by 3.

Both 2 and 3 are prime factors, thus it is impossible for

the transformation.

Edited by Dej Mar

Share this post


Link to post
Share on other sites

Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account.

Guest
Answer this question...

×   Pasted as rich text.   Paste as plain text instead

  Only 75 emoji are allowed.

×   Your link has been automatically embedded.   Display as a link instead

×   Your previous content has been restored.   Clear editor

×   You cannot paste images directly. Upload or insert images from URL.

Loading...
Sign in to follow this  

  • Recently Browsing   0 members

    No registered users viewing this page.

×
×
  • Create New...